A matemática moderna no Brasil: as primeiras experiência e propostas de seu ensino - Borges, Rosimeire Aparecida Soares (2005)
The present work had as objective to study the Movement of the Modern Mathematics (MMM) under a new angle, the one of the teacher D Ambrosio s works, related to the Mathematics teaching in the brazilian secondary, written in 1957,1959 and 1961. Those articles compound the Personal Ubiratan D Ambrosio File APUA. As a support to the present research, some relevant works by brazilian authors were studied too referring to MMM, and as complement, there were interviews with the teacher D Ambrosio in the years of 2003, 2004 and 2005. That teacher was chosen due to his work in the secondary mathematics teaching, along the period that preceded the movement. After the analysis and comparisons, there was made the intersection of theses studies, what made it possible to investigate the pedagogical possibilities in the mathematics subjects, in the classroom environment, in that period. The theoretical support was given by authors, such as Nóvoa and Freitas, that allowed us to analyze the varied shortcuts that drew the map of the Movement, starting from the history of the teacher's life, showed in his recent interview. But that, we could infer that not only the proposals of MMM, but also the teacher D Ambrosio s ones, that had very similar initial intentions and could contribute to the teaching/learning changes in the Mathematics area. However, those ideas became quite distant to the pedagogical practice level. The necessary ways to the accomplishment of those proposals, should have been build among teachers, students and school, considering the expectations towards the Mathematics subject and the social cultural brazilian reality, in that time